Training Of Trainer (TOT) â€œHydroponic Cultivation Techniquesâ€ for MTs Baitul Hikmah Tempurejo Jember Teachers - ,, Iswahyono (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Community interest, especially the younger generation working in agriculture, continues to decline. The lack younger generation's interest in the agricultural sector is due to the image of being filthy and hot during work, in such a way that innovations in cultivation systems are required. Hydroponic technology is one of the solutions and could be introduced to the younger generation from an early age. This community service aims to produce trainers of hydroponics from MTs Baitul Hikmah Tempurejo Jember teachers and increase student interest in hydroponic cultivation extracurricular activities. The implementation of the training focused on teachers. After learning hydroponic cultivation techniques, the teacher and the community service team explain and demonstrate to the student. The training materials include understanding hydroponic cultivation, keys to success in hydroponics, the practice of preparing hydroponic tools, materials and installation; the method of seeding and preparation of nutrients; the technique of maintenance and harvesting. This community service has produced 8 teachers as trainers, a package of facilities and infrastructure for hydroponic cultivation, and a significant increase in student interest in hydroponic cultivation extracurricular activities